Construction of chitosan-supported nickel cobaltite composite for efficient electrochemical capacitor and water-splitting applications - Shymaa S. Medany; Ayman Nafady; Razium Ali Soomro; Mahmoud A. Hefnawy (Scientific Reports, 2024)
Abstract The construction of highly efficient electrode material is of considerable interest, particularly for high capacitance and water-splitting applications. Herein, we present the preparation of a NiCo2O4-Chitosan (NC@Chit) nanocomposite using a simple hydrothermal technique designed for applications in high capacitance and water-splitting. The structure/composition of the NC@Chit composite was characterized using different analytical methods, containing electron microscope (SEM and TEM), and powder X-ray diffraction (XRD). When configured as an anode material, the NC@Chit displayed a high capacitance of 234 and 345 F g−1 (@1Ag−1 for GC/NC and NC@Chit, respectively) in an alkaline electrolyte. The direct use of the catalyst in electrocatalytic water-splitting i.e., HER and OER achieved an overpotential of 240 mV and 310 mV at a current density of 10 mA cm−2, respectively. The obtained Tafel slopes for OER and HER were 62 and 71 mV dec−1, respectively whereas the stability and durability of the fabricated electrodes were assessed through prolonged chronoamperometry measurement at constant for 10 h. The electrochemical water splitting was studied for modified nickel cobaltite surface using an impedance tool, and the charge transfer resistances were utilized to estimate the electrode activity.